Station Rotation: An Experience Report of a Teaching-Learning Proposal in Youth and Adult Education - da Silva, Regiane Aparecida (2023)
Objective. The objective of this investigation was to verify the possibilities and potentialities of the use of active methodologies (AM), with a focus on rotation by stations, in Youth and Adult Education (YAE). The study also aimed to suggest AM as a proposal that collaborates with quality in teaching-learning and can contribute to students becoming autonomous subjects. Since it is an audience that needs more attention from researchers in the area of education, from this the practice in question was carried out in a six-class municipal school with 112 students in the center-west of Goiás. The class chosen for the practice has 28 students enrolled, and two are from Inclusive Education. Methodology. In the data collection, we used questionnaires, and the data collected were analyzed in a discursive way. For this research, we used a qualitative approach of the descriptive type and documental analysis of public policies. Conclusions. It is concluded that the applied practice must gradually be inserted into the education of young people and adults, collaborating with the student to facilitate learning and with the teacher, who is always looking for new ways to meet your student.